2017
DOI: 10.3897/zookeys.672.10078
|View full text |Cite
|
Sign up to set email alerts
|

The selection by the Asiatic black bear (Ursus thibetanus) of spring plant food items according to their nutritional values

Abstract: The present study aimed to investigate the nutritional aspects of the bear diet quantitatively, in order to understand plant food selection in spring. Bears were observed directly from April to July in 2013 and 2014, to visually recognize plant species consumed by bears, and to describe the foraging period in the Ashio-Nikko Mountains, central Japan. Leaves were collected from eight dominant tree species, regardless of whether bears fed on them in spring, and their key nutritional components analyzed: crude pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Food items for which bears spent a longer time foraging (longer number of continuous clips) had a higher fecal relative frequency in the fecal analysis. Prior studies using fecal analysis have reported that the soft mast of Cerasus are one of principal foods in this season ( Koike 2010 ; Furusaka et al 2017 ). Presence of the soft mast of Cerasus was confirmed to be consumed by bears at a high relative frequency by both the methods and when using longer continuous clips.…”
Section: Discussionmentioning
confidence: 99%
“…Food items for which bears spent a longer time foraging (longer number of continuous clips) had a higher fecal relative frequency in the fecal analysis. Prior studies using fecal analysis have reported that the soft mast of Cerasus are one of principal foods in this season ( Koike 2010 ; Furusaka et al 2017 ). Presence of the soft mast of Cerasus was confirmed to be consumed by bears at a high relative frequency by both the methods and when using longer continuous clips.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous leaf unfolding and fruiting seeds of the Fagaceae family supply moderate or abundant foods for Asiatic black bears in spring and autumn, respectively, resulting in low dietary specialization. In contrast, low-nutritional green vegetation with high fiber content [38] and slightly fleshy fruits are available in summer, that is, food is scarce (especially in July), resulting in high dietary specialization (Figs 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, male bears occupy a larger home range (more than 50 km 2 ) as compared to females (12 to 50 km 2 ) (Rogers, 1977;Young and Ruff, 1982;Ali et al, 2015). The breeding process occurs from May to June, while cubs (one to five) are born from early December to late February and cubs stay with their mother for 12 to 20 months (Stevens and Lofts, 1988;Waseem and Ali, 2011;Furusaka et al, 2017;Hamasaki et al, 2020;Deus et al, 2021;Hamasaki and Dan, 2021;McCormack and Cotoras, 2021). The presence of black bear can also be determined from the pattern of feeding including claw marks, broken branches, soil digging for termites, and bark removal from the trees that are used as a food source during the winter season (Servheen, 1990;Crooks et al, 2011;Cardinale et al, 2012).…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%